Auggie & me : three Wonder stories - Palacio, R. J. (New York : Alfred A. Knopf, 2015)
"These stories are an extra peek at Auggie, a boy born with extreme facial abnormalities, before he started at Beecher Prep and during his first year there. Readers get to see him through the eyes of Julian, the bully; Christopher, Auggie's oldest friend; and Charlotte, Auggie's new friend at school"-- Provided by publisher
Keywords: Friendship Fiction; Interpersonal relations Fiction; Children's stories